2017
DOI: 10.1037/xhp0000434
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the internal geometry of tactile space.

Abstract: A large body of research has shown spatial distortions in the perception of tactile distances on the skin. For example, perceived tactile distance is increased on sensitive compared to less sensitive skin regions, and larger for stimuli oriented along the medio-lateral axis than the proximo-distal axis of the limbs. In this study we aimed to investigate the spatial coherence of these distortions by reconstructing the internal geometry of tactile space using multidimensional scaling (MDS). Participants made ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
79
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

5
1

Authors

Journals

citations
Cited by 40 publications
(92 citation statements)
references
References 84 publications
13
79
0
Order By: Relevance
“…(Note that for this 108 and other tests involving ratios, the calculation of means and all statistical tests were 109 conducted on log-transformed values, which were converted back to ratios to report mean 110 values). As predicted, this result replicates the anisotropy in tactile distance perception 111 previously reported on the hand dorsum (Longo & Golubova, 2017;Longo & Haggard, 2011). 112 113 fMRI data 114 The main aim of this study was to identify the neural bases of these distorted 115 perceptual spatial configuration of the skin surface.…”
supporting
confidence: 78%
See 4 more Smart Citations
“…(Note that for this 108 and other tests involving ratios, the calculation of means and all statistical tests were 109 conducted on log-transformed values, which were converted back to ratios to report mean 110 values). As predicted, this result replicates the anisotropy in tactile distance perception 111 previously reported on the hand dorsum (Longo & Golubova, 2017;Longo & Haggard, 2011). 112 113 fMRI data 114 The main aim of this study was to identify the neural bases of these distorted 115 perceptual spatial configuration of the skin surface.…”
supporting
confidence: 78%
“…191 193 In the present study, we reconstructed the internal geometry of tactile space using 194 representational similarity of neural patterns between locations on the skin. Behaviorally, we 195 replicated previous reports that tactile space is stretched along the medio-lateral axis of the 196 hand dorsum (e.g., Longo & Golubova, 2017;Longo & Haggard, 2010. Critically, using a 197 novel approach that combine fMRI with MDS, we showed that similar distortions can be 198 measured directly from neural data.…”
supporting
confidence: 76%
See 3 more Smart Citations